Emergency department presentations with suicide and self-harm ideation: a missed opportunity for intervention?. (18th April 2023) - Ross, E.; Murphy, S.; O'Hagan, D.; Maguire, A.; O'Reilly, D.
Abstract: Aims: Suicidal ideation constitutes a central element of most theories of suicide and is the defining facet separating suicide from other causes of death such as accidents. However, despite a high worldwide prevalence, most research has focused on suicidal behaviours, such as completed suicide and suicide attempts, while the greater proportion who experienced ideation, which frequently precedes suicidal behaviour, have received much less attention. This study aims to examine the characteristics of those presenting to EDs with suicidal ideation and quantify the associated risk of suicide and other causes of death. Methods: Retrospective cohort study was performed based on population-wide health administration data linked to data from the Northern Ireland Registry of Self-Harm and centrally held mortality records from April 2012 to December 2019. Mortality data, coded as suicide, all-external causes and all-cause mortality were analysed using Cox proportional hazards. Additional cause-specific analyses included accidental deaths, deaths from natural causes and drug and alcohol-related causes. Results: There were 1, 662, 118 individuals aged over 10 years, of whom 15, 267 presented to the ED with ideation during the study period. Individuals with ideation had a 10-fold increased risk of death from suicide (hazard ratio [HRadj ] = 10.84, 95% confidence interval [CI] 9.18, 12.80) and from all-external causes (HRadj = 10.65, 95% CI 9.66, 11.74) and a threefold risk of death from all-causes (HRadj = 3.01, 95% CI 2.84, 3.20). Further cause-specific analyses indicated that risk of accidental death (HRadj = 8.24, 95% CI 6.29, 10.81), drug-related (HRadj = 15.17, 95% CI 11.36, 20.26) and alcohol-related (HRadj = 10.57, 95% CI 9.07, 12.31) has also significantly increased. There were few socio-demographic and economic characteristics that would identify which of these patients are most at risk of suicide or other causes of death. Conclusions: Identifying people with suicidal ideation is recognized to be both important but difficult in practice; this study shows that presentations to EDs with self-harm or suicide ideation represent an important potential intervention point for this hard-to-reach vulnerable population. However, and unlike individuals presenting with self-harm, clinical guidelines for the management and recommended best practice and care of these individuals are lacking. Whilst suicide prevention may be the primary focus of interventions aimed at those experiencing self-harm and suicide ideation, death from other preventable causes, especially substance misuse, should also be a cause of concern.